Comparison between quasi-analytical solution and a numerical analysis of unsaturated flow equation - S. Awadalla, (1989)
The unsaturated flow equation in one dimension has been solved using two types of techniques. The first technique involves the solving of the partial differential equation for flow in rigid unsaturated porous media using implicit finite difference approach. The second technique is based on step function model and is solved by developing the Green and Ampt approach. Both techniques are used to calculate the amount of water drained from initially saturated profile to a moving water table